Pemanfaatan Media Papan Pintar Numerasi untuk Meningkatkan Kemampuan Berhitung pada Anak Usia 6-7 Tahun - Wilhelmina Menge; Efrida Ita; Andi Nafsia; Elisabeth Tantiana Ngura (Lembaga Pendidikan Islam Ma'aarif NU Kabupaten Magetan, 2024)
This study aims to determine the use of numeracy smart board media in improving numeracy skills in children aged 6-7 years at Kekajodho Catholic Elementary School. This type of research is qualitative descriptive. The object of the research is 6-7 years old students in grade 1 totaling 10 people. The methods used in this study are observation, interviews and documentation of changes in the child's speed, accuracy, concentration and focus in completing mathematical calculations before and after the use of the smart board. The results showed that there was an increase in counting speed, where children were able to solve problems faster after getting repeated exercises using the learning media. In addition, children's accuracy in counting has increased, which is characterized by a reduction in errors in calculations after getting direct feedback from the smart board. Children's concentration and focus also improve, with longer attention duration and better engagement during the learning process. This study concludes that the use of numeracy smart boards is effective in improving early childhood numeracy skills, and is expected to be applied more widely in mathematics learning in elementary schools.